Invader Strategies in the War of Attrition with Private Information - Lars Peter Metzger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
Second price allpay auctions (wars of attritions) have an evolutionarily stable equilibrium in pure strategies if valuations are private information. I show that for any level of uncertainty there exists a pure deviation strategy close to the equilibrium strategy such that for some valuations the equilibrium strategy has a selective disadvantage against the deviation if the population mainly plays the deviation strategy. There is no deviation strategy with this destabilizing property for all valuations if the distribution of valuations has a monotonic hazard rate. I argue that in the Bayesian game studied here, a mass deviation can be caused by the entry of a small group of agents. Numeric calculations indicate that the closer the deviation strategy to the equilibrium strategy, the less valuations are destabilizing. I show that the equilibrium strategy does not satisfy continuous stability.
Keywords: C72; C73; D44; 330; Continuous Strategies; Evolutionary Stability; War of Attrition; Strict Equilibrium; Neighborhood Invader Strategy; Continuous Stability; Evolutionary Robustness